1990
DOI: 10.1051/animres:19900106
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids and starch digestibility and true metabolizable energy content of raw and extruded jackbeans (Canavalia ensiformis) in adult cockerels

Abstract: Summary — Four experiments were conducted with adult cockerels to determine digestibility of amino acids, starch digestibility and true metabolizable energy in ground raw (RJB) and extruded (EJB) jackbean seeds. Three feeding methods were used: ad libitum feeding, dry and wet force feeding.Both RJB and EJB were tested alone or at 3 levels of inclusion, 10, 30

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Thus, Leon et al (1990) found that the AMEN content of raw canavalia was 11.6 MJ/kg whereas, after extrusion, the ME value rose to 13.3 MJ/kg. However, the values reported by DMello et al (1985) and Leon et al (1986) of 11.8 and 10.5 MJ/kg, respectively, are rather lower than those quoted by Leon et al (1989a).…”
Section: Protcinmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, Leon et al (1990) found that the AMEN content of raw canavalia was 11.6 MJ/kg whereas, after extrusion, the ME value rose to 13.3 MJ/kg. However, the values reported by DMello et al (1985) and Leon et al (1986) of 11.8 and 10.5 MJ/kg, respectively, are rather lower than those quoted by Leon et al (1989a).…”
Section: Protcinmentioning
confidence: 94%
“…Although it has been suggested that non-structural carbohydrates in legume seeds are not well utilised by monogastric animals, either because of differences in the amylose-amylopectin ratio of the starch (Rao and Rao, 1978) or because of the presence of heteropolysaccharides and oligosaccharides (Bell, 19781, data published by DMello et al (1985) and Leon et al (1990) have shown that canavalia carbohydrates are a good source of energy with starch and amylose contents of about 287-350 g/kg (Molina and Bressani, 1975;Kay, 1979;Ledn et al, 1989a).…”
Section: Protcinmentioning
confidence: 99%
“…The adverse effect of jack beans in animal diets has been attributed in part to the presence of canavanine (Escobar et al 1983;D'Mello et al 1985;Kessler et al 1990) and/or the formation of canaline following the ingestion of canavanine (Acamovic & D'Mello 1990). Whereas heat treatment is considered to be an effective means of inactivating concanavalin-A (Kessler et al 1990;Leon et al 1990;Huisman & Tolman 1992) the stability of canavanine at temperatures up to 184 °C (Merck 1989) requires an alternative strategy for detoxification. Other procedures investigated include a combination of heat treatment with soaking in water or soaking and shaking (D'Mello et al 1985;Leon et al 1987), ensiling with urea and/or ammonia (Montilla et al 1981), alcohol extraction (Martinez et al 1988), acid extraction (Martinez et al 1988;Ologhobo et al 1993) and alkaline extraction (D 'Mello & Walker 1991;Ologhobo et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…These findings align with the results reported by D'mello et al [15], who discovered that jackbeans soaked in water for 20 hours at 40°C, minced, and autoclaved for 1 hour, had the highest AME value of 2814.2 kcal/kg, and the highest N-corrected AME value of 2868 kcal/kg. Additionally, Leon et al [16] reported an increase in the value of N-corrected TME from 2771 kcal/kg in raw jackbeans to 3183 kcal/kg in extruded jackbeans tested in adult cockerels.…”
Section: Metabolic Energy and Digestible Proteinmentioning
confidence: 99%